The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-1-4939-6872-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Reporter Systems to Study HTLV-1 Transmission

Abstract: The retrovirus Human T-lymphotropic virus type 1 (HTLV-1) preferentially infects CD4 T-cells via cell-to-cell transmission, while cell-free infection of T-cells is inefficient. Substantial insights into the different routes of transmission have largely been obtained by imaging techniques or by flow cytometry. Recently, strategies to quantify infection events with HTLV-1 improved. In this chapter, we present two different methods to quantitate virus transmission. Both methods are based on measuring gene activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Assuming similar structures for the RNA-terphenyl complexes, this suggested that 1a and 1d had greater affinity for loop IIB relative to 3c, in line with the results obtained with fluorescence experiments. We also detected intermolecular NOEs between H1' of the extrahelical A19 loop nucleotide and the aminoethyl protons of compound 1a, implying that the ligand associated to the loop from the major groove side, as observed for Rev [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Fig. 1C) 11,12 .…”
Section: Synthesis Of 14-terphenyl Compoundsmentioning
confidence: 71%
See 4 more Smart Citations
“…Assuming similar structures for the RNA-terphenyl complexes, this suggested that 1a and 1d had greater affinity for loop IIB relative to 3c, in line with the results obtained with fluorescence experiments. We also detected intermolecular NOEs between H1' of the extrahelical A19 loop nucleotide and the aminoethyl protons of compound 1a, implying that the ligand associated to the loop from the major groove side, as observed for Rev [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Fig. 1C) 11,12 .…”
Section: Synthesis Of 14-terphenyl Compoundsmentioning
confidence: 71%
“…The terminal synthons were aryl bromides bearing nitrile groups on the two side chains as masked amines, ready to be revealed in later steps, whereas the central synthon presented two alkyl side chains and two boronic esters. A simple double palladium-catalyzed Suzuki-Miyaura cross-coupling between two terminal synthons to every one central synthon constructed the desired terphenyl scaffold, and a subsequent borane-mediated reduction of the nitrile groups resulted in the amines required to mimic the arginine residues in Rev [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Fig. S1).…”
Section: Synthesis Of 14-terphenyl Compoundsmentioning
confidence: 99%
See 3 more Smart Citations